Analisis Studi Pustaka: Pentingnya Melakukan Asesmen Intelegensi kepada Peserta Didik sebelum Memberikan Tindakan dalam Pemilihan Jurusan Lebih Lanjut - Bariza, Marwa Fuha Alilatul; Mufidah, Cindy Imroatul; Sholekhah, Adistya Aliyus (Lembaga Yasin AlSys, 2025)
The selection of academic tracks at the senior high school (SMA) level is a crucial phase in determining students’ educational pathways and future careers. However, many students experience confusion during this process due to a lack of understanding of their own potential and abilities. This study aims to analyze the urgency of implementing intelligence assessments prior to track selection, using a literature review approach. Intelligence assessments provide objective information about students’ cognitive capacities, including logical reasoning, information processing, and dominant learning styles. The findings indicate that intelligence testing can support more informed decision-making, enhance self-confidence, and reduce the risk of students being placed in unsuitable academic tracks. Nevertheless, such assessments have limitations, including the exclusion of non-cognitive aspects such as interests, motivation, and personal values, and are also susceptible to emotional states and cultural biases. Therefore, intelligence assessments should be implemented comprehensively alongside interest and aptitude assessments to yield more accurate and student-relevant outcomes. This study recommends that schools integrate intelligence assessments into academic tracking policies as a means to support more purposeful and potential-aligned student decisions.